2020
DOI: 10.48550/arxiv.2006.15390
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Stabilization of a Continuous Limit of the Ensemble Kalman Inversion

Abstract: The ensemble Kalman filter belongs to the class of iterative particle filtering methods and can be used for solving control-to-observable inverse problems. In recent years several continuous limits in the number of iteration and particles have been performed in order to study properties of the method. In particular, a one-dimensional linear stability analysis reveals a possible instability of the solution provided by the continuous-time limit of the ensemble Kalman filter for inverse problems. In this work we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 25 publications
(82 reference statements)
0
17
0
Order By: Relevance
“…Note that within this limit the noise is scaled with 1 ∆t which allows for the continuous time limit. Further, the term D G vanishes leading to possibly unstable dynamics [27,5].…”
Section: Continuous-time Limitmentioning
confidence: 99%
See 3 more Smart Citations
“…Note that within this limit the noise is scaled with 1 ∆t which allows for the continuous time limit. Further, the term D G vanishes leading to possibly unstable dynamics [27,5].…”
Section: Continuous-time Limitmentioning
confidence: 99%
“…For the rigorous mean-field derivation and analysis of the EKI we refer to [10,16]. Equation ( 9) is a nonlinear transport equation arising from non-linear gradient flow interactions and in [10,5] it is observed that the counterpart of (8) holds at the kinetic level. In fact, for…”
Section: Mean-field Limitmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence the evolution of the whole ensemble and the sample means can be seen as minimizing movement discretization of the gradient flow of the functional u → 1 2 Au − ỹ 2 Γ with respect to the varying norm • 2 C(un) , see for example the discussion in [1] and also [25].…”
Section: Introductionmentioning
confidence: 99%